﻿Pleurophragmium parvisporum (Ascomycota): One name, seven stories - a case highlighting the need for verification of strains from public culture collections - Réblová, Martina; Nekvindová, Jana; Bauchová, Lucie; Hernández-Restrepo, Margarita (IMA fungus, 2025)
Public repositories of living fungal strains provide essential reference points and support diverse scientific outcomes. Current best practices for preserving fungal strains emphasise the generation of DNA barcodes and the management of comprehensive metadata. However, challenges arise when type material or authentic reference strains are lacking, as this prevents direct comparison of DNA barcodes and forces identifications to rely solely on morphology. This problem is particularly pronounced for strains deposited during the pre-molecular era, especially those belonging to species with simple or convergent morphologies. In this study, we re-examined seven strains deposited in a public culture collection under the name Pleurophragmium parvisporum, including synonymous designations. Our approach combined cultivation experiments, comparative morphological analyses, multi-locus phylogenetic reconstruction of six nuclear markers, and biogeographic assessments. Our analyses revealed that these strains are scattered across four distinct families or orders in three classes. Two strains belong to Thysanorea (Chaetothyriales, Eurotiomycetes): T. acropleurogena sp. nov. and a sterile strain identified as the already known T. melanica. Two other strains were resolved within Wongia (Papulosaceae incertae sedis, Sordariomycetes) and introduced as W. pallidopolaris sp. nov. and W. rhachidophora sp. nov. Finally, two strains represent novel taxa within the Tubeufiales (Dothideomycetes), described here as Zaanenomyces hilifer sp. nov. and Skoliomycella flava gen. et sp. nov. Of the seven examined strains, only one conformed to the species concept of P. parvisporum and is here regarded as its reference strain. The phylogenetic analyses resolved P. parvisporum within Neomyrmecridium (Myrmecridiales, Sordariomycetes). Consequently, Neomyrmecridium was reduced to synonymy of Pleurophragmium, leading to the proposal of 11 new combinations (P. asiaticum comb. nov., P. asymmetricum comb. nov., P. fusiforme comb. nov., P. gaoligongense comb. nov., P. guizhouense comb. nov., P. luguense comb. nov., P. naviculare comb. nov., P. pteridophytophilum comb. nov., P. septatum comb. nov., P. sichuanense comb. nov., and P. sorbicola comb. nov.), and two new names (P. fluviale nom. nov. and P. jiulongheense nom. nov.). In addition, three species formerly placed in Uncispora are transferred to Thysanorea, with new combinations proposed based on congruent morphology and multi-locus phylogenetic evidence: T. hainanensis comb. nov., T. sinensis comb. nov., and T. wuzhishanensis comb. nov. This study refines the generic limits of Pleurophragmium and morphologically similar genera and reveals several previously unrecognised lineages. It highlights how misinterpretation of subtle morphological features may lead to strains being misidentified and deposited under incorrect names in public collections, where they risk perpetuating taxonomic errors.
Keywords: holoblastic-denticulate conidiogenesis; phylogenetics; new taxa; saprobic; systematics; Dactylaria; Ascomycota; repository; DNA barcode